Nivolumab‐induced liver injury with a steroid‐refractory increase in biliary enzymes, in a patient with malignant mesothelioma: An autopsy case report. Issue 12 (23rd December 2021) - Arai, Kazumori; Matsuda, Masanori; Nakayasu, Hiromasa; Meguro, Shiori; Kurokami, Takafumi; Kubota, Aki; Iwasaki, Tomohiro; Suzuki, Makoto; Kawaguchi, Shinya; Iwashita, Toshihide
Abstract: This is the first autopsy report of hepatotoxicity from nivolumab immunotherapy for malignant mesothelioma. The increase in levels of biliary enzymes and randomly distributed endothelial damage were steroid‐refractory, but second‐line option was abandoned because of cachexia. Further discussions are needed regarding the customized management of immune‐related toxicities. Abstract : Further discussions are needed to manage immune‐related hepatotoxicity with a steroid‐refractory increase in biliary enzymes and/or cancer complications. Management tailored to the conditions of individuals will be important in future.